Problems of psychological assistance to cancer patients - R. N. Mustafin (Сибирский онкологический журнал)
Purpose of the study: to assess the problem of psychological assistance to cancer patients and ways to resolve this problem. Material and Methods. The search for relevant sources was carried out in Scopus, Web of Science, PubMed, elibrary, including publications from February 2005 to December 2023. Of the 534 scientific articles found, 53 were used to write the systematic review. Results. Cancer patients are characterized by a high incidence of anxiety, depressive disorders and suicidal thoughts. Research in recent decades has shown that although more than a third of cancer patients experience stress and more than half experience depression and anxiety due to a cancer diagnosis, many do not seek psychological help to address their problems. Stress leads to an increased risk of comorbid psychological disorders and suboptimal compliance with anticancer therapy, potentially leading to decreased health and chance of recovery. In addition, psychological well-being is a necessary component for the recovery of the patient’s body after therapy, especially with a favorable prognosis. Research has shown that relatives caring for terminal cancer patients also need psychological help. active use of the work of a psychologist in the treatment of cancer patients will improve treatment results, improve the quality of care provided and comply with the principles of personalized medicine. to optimize the provision of psychological assistance, it is necessary to take measures to expand and make it accessible, for which the optimal methods are to regulate it in the treatment plan for cancer patients. Conclusion. In the current healthcare system, it is necessary to widely introduce consultations with psychologists in the treatment of cancer patients, which will increase the effectiveness of therapy and patient survival. the task of the oncologist is to identify patients with psychological disorders, especially those prone to suicidal behavior, anxiety and depression, and to correctly explain to them the need to receive psychological help, thanks to which the patient will not only be able to get rid of his emotional problems, but will also make sure that he needs to continue the treatment prescribed by the doctor.